Polyester release film
A polyester release film with bimodal and unimodal particle distributions addresses surface roughness issues in MLCCs, enhancing transfer quality and productivity by reducing dust and scratches.
Patent Information
- Application Number
- JP2024540601
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-19
- Filing Date
- 2023-01-11
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-01-11
AI Technical Summary
Existing polyester release films for ceramic multilayer capacitors (MLCCs) face issues with surface roughness affecting transfer quality, leading to particle detachment, scratches, and poor coating stability, especially as capacitors become smaller and thinner.
A polyester release film with a bimodal and unimodal particle size distribution on opposite sides, providing specific surface roughness and particle compositions to enhance slip and winding properties, reduce cutting dust, and prevent pinholes.
The film achieves improved handling, reduced dust generation, and enhanced productivity by minimizing scratches and pinholes during high-speed transfer and winding, suitable for thin ceramic sheets.
Smart Images

Figure 2024546354000001 
Figure 2024546354000002 
Figure 2024546354000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester-based release film, for example, a laminated polyester-based release film for surface protection used in electronic materials such as multi-layer ceramic condensers (hereinafter, referred to as MLCC), polarizing plate protection, and OCA. [Background technology]
[0002] Polyester film has excellent thermal stability, chemical resistance, mechanical strength, surface properties, and thickness uniformity, making it suitable for a variety of uses and process conditions.
[0003] Due to these properties, polyester films are used in applications such as capacitors, photographic films, labels, pressure reducing tapes, decorative laminates, transfer tapes, polarizing plates, and ceramic release green sheets.
[0004] In particular, in the case of ceramic multilayer capacitors, as the capacitors become smaller, the thickness of the green sheets (release films) becomes thinner and thinner. This inevitably increases the effect of the physical properties of the green sheets on the ceramic capacitors.
[0005] For example, if the surface roughness of the green sheet is high, the protruding shape may be transferred to the ceramic sheet. Also, when the green sheet is brought into contact with a transfer roll and transferred at high speed, particles may come off and become cutting powder, which may stick to the contacting roll, causing contamination and scratches. Also, the cutting powder and the detached particles may adhere to the transfer roll, causing scratches on the surface of the green sheet, and become foreign matter in the subsequent process.
[0006] Conversely, if the surface roughness of the green sheet is too low, the coating stability when coating the ceramic slurry, the running property and slip property of the film are reduced, and scratches may occur when the green sheet is wound on a roll.
[0007] Therefore, as described above, by developing a green sheet (release film) with excellent surface properties, it is possible to improve slip characteristics, improve winding properties around a roll, and prevent the occurrence of cutting powder and scratches. However, there is still much room for improvement in the surface properties of green sheets, and the need for this is currently increasing as ceramic capacitors become smaller and thinner. Summary of the Invention [Problem to be solved by the invention]
[0008] One embodiment of the present invention provides a polyester-based release film for surface protection used in electronic materials such as multilayer ceramic capacitors (MLCCs), polarizing plate protection, and OCA.
[0009] In one embodiment, the release film is a polyester-based release film that is a thin film having a thickness of 50 μm or less so that it can be applied to a release film for a thin-film ceramic multilayer capacitor (MLCC), yet has excellent winding properties and slip properties when rolled up.
[0010] In one embodiment, the release film provides a polyester-based release film that reduces the occurrence of pinholes when a thin ceramic sheet is manufactured by coating a ceramic slurry.
[0011] The present invention also provides a polyester release film which produces little cutting powder even when transported at high speed during film production, generates little dust when cutting the film, and does not produce scratches when taken up. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention can provide a polyester-based release film that is laminated with a polyester base film, a polyester surface layer containing particles having a bimodal particle size distribution on one side thereof, and a polyester surface layer containing particles having a unimodal particle size distribution on the other side thereof.
[0013] According to one embodiment of the present invention, the surface layer including the particles having a bimodal particle size distribution may have a surface roughness (Ra) of 0.010 to 0.030 μm.
[0014] According to one aspect of the present invention, the surface roughness (Ra) of the surface layer including the particles having a unimodal particle size distribution may be 0.001 to 0.015 μm.
[0015] According to one embodiment of the present invention, the average particle size of the particles in the surface layer including the bimodal particles may be 0.05 to 2 μm.
[0016] According to one embodiment of the present invention, the average particle size of the particles in the surface layer including the particles having a unimodal particle size distribution may be 0.03 to 1 μm.
[0017] According to one embodiment of the present invention, the content of the particles in the surface layer may be 300 to 5,000 ppm.
[0018] According to one embodiment of the present invention, the particles may include a mixture of one or more particles selected from inorganic particles and organic particles.
[0019] According to an embodiment of the present invention, the inorganic particles may be one or more selected from the group consisting of metal oxides, metal carbides, metal sulfides, and metal carbonitrides.
[0020] According to one embodiment of the present invention, the organic particles may include any one or a mixture of two or more selected from silicone resin, crosslinked acrylic particles, crosslinked polystyrene particles, benzoguanamine-formaldehyde resin, benzoguanamine-melamine-formaldehyde resin, and melamine-formaldehyde resin.
[0021] According to one aspect of the present invention, the polyester may include a polyethylene terephthalate resin.
[0022] According to one aspect of the present invention, there can be provided a polyester-based release film, wherein the release film is produced by coextrusion.
[0023] According to one aspect of the present invention, the method may further include producing the film by stretching after the co-extrusion. Effect of the Invention
[0024] The polyester-based release film of the present invention according to one embodiment has excellent winding properties and slip properties on a roll even though it is a thin film, and can provide the effect of reducing the occurrence of pinholes when a thin ceramic sheet is produced by applying a ceramic slurry.
[0025] Furthermore, a polyester-based release film can be provided that generates little cutting powder even when transported at high speed during the production of films such as MLCCs, and that generates little dust when cutting the film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will be described in more detail below. However, the following specific examples or examples are merely a reference for explaining the present invention in detail, and the present invention is not limited thereto, and may be realized in various forms.
[0027] In addition, unless otherwise defined, all technical and scientific terms have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. In the present invention, the terms used in the description are merely for the purpose of effectively describing specific embodiments, and are not intended to limit the present invention.
[0028] Additionally, as used in the specification and the appended claims, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0029] Furthermore, when a part "comprises" certain elements, this means that it can further include other elements, but not excluding other elements, unless specifically stated to the contrary.
[0030] In the present invention, the term "bimodal" refers to a mixture of inorganic particles having different average particle sizes, or a mixture having two peaks or a shoulder peak in particle size distribution.
[0031] Each of the configurations of the present invention will be described in more detail below.
[0032] According to one embodiment, the release film of the present invention is achieved by preparing a polyester laminate film in which a polyester surface layer containing particles having a bimodal particle size distribution is laminated on one side of a polyester base film, and a polyester surface layer containing particles having a unimodal particle size distribution is laminated on the other side of the polyester base film.
[0033] In one embodiment, the release film is preferably a laminated polyester-based laminate film as follows, since the above object can be better achieved: That is, the polyester surface layer containing particles having a bimodal particle size distribution on one side of the polyester base film may have a surface roughness (Ra) of 0.010 to 0.030 μm, and the release film is preferably a laminated polyester-based laminate film in which a polyester surface layer containing particles having a unimodal particle size distribution and having a surface roughness (Ra) of 0.001 to 0.015 μm is laminated on the other side of the base film, since the above object can be better achieved.
[0034] In one embodiment, the release film employs a polyester surface layer having an essentially bimodal distribution obtained by mixing two types of inorganic or organic particles having different average particle sizes on one side of a polyester base film, and a polyester surface layer using particles having a single particle size distribution on the other side. This has resulted in the discovery that a release film can be provided that has a flat surface, but includes effective protrusions that can improve handling properties during post-processing and winding properties of the film, generates little dust during cutting, and is a green sheet that does not generate scratches during winding. This has led to the completion of the present invention.
[0035] In one embodiment, in the release film, a surface layer containing particles having a bimodal particle size distribution and having a surface roughness (Ra) of 0.010 to 0.030 μm on one side of the polyester base film and a surface layer containing particles having a unimodal particle size distribution and having a surface roughness (Ra) of 0.001 to 0.015 μm on the other side of the base film are laminated. In order to provide such a laminated polyester film, the unimodal particles in one surface layer of the laminate film have an average particle size (D mean It is more preferable that particles having a diameter of 0.03 μm to 1 μm are added to the surface layer in an amount of 300 to 5,000 ppm, since this shows better physical properties.
[0036] In one embodiment, the polyester resin used in the base film and both surface layers is not particularly limited, and may be a normal polyester resin, specifically, for example, a polyester resin obtained by polycondensation of an acid component mainly composed of a dicarboxylic acid and a glycol component mainly composed of an alkylene glycol.
[0037] The dicarboxylic acid is not limited, but may be terephthalic acid or its alkyl ester or phenyl ester, and may be partially substituted with a difunctional carboxylic acid or its ester-forming derivative, such as isophthalic acid, oxyethoxybenzoic acid, adipic acid, sebacic acid, and 5-sodium sulfoisophthalic acid.
[0038] In addition, the glycol component is not limited, but ethylene glycol is mainly used, and propylene glycol, neopentyl glycol, trimethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,4-bisoxyethoxybenzene, bisphenol, polyoxyethylene glycol, etc. may be used in combination, and a monofunctional compound or a trifunctional compound may be used in combination.
[0039] In addition, the composition may contain one or more additives that are commonly used in the polymerization of polyester resins, i.e., a pinning agent, an antistatic agent, an ultraviolet stabilizer, a waterproofing agent, a slip agent, and a heat stabilizer, but is not limited thereto.
[0040] In one embodiment of the present invention, the polyester resin may be polyethylene terephthalate. That is, the polyester resin may be polyethylene terephthalate prepared by using terephthalic acid as a dicarboxylic acid and ethylene glycol as a glycol. It may also be a polyethylene terephthalate copolymer. The polyester resin may be prepared by a TPA (Terephthalic acid) polymerization method or a DMT (dimethyl terephthalate) polymerization method, which are conventional polymerization methods in the art, but is not limited thereto.
[0041] In one embodiment, the release film has a laminated structure with different surface characteristics on both sides of the polyester base film. By adjusting a specific surface roughness using particles with different characteristics, dust is not generated when the film is cut, and the transfer of the surface roughness of both sides prevents the occurrence of pinholes and thickness unevenness in the layer applied to the release layer. At the same time, handling properties such as roll running property and winding property are improved, thereby greatly improving productivity.
[0042] In one embodiment, the surface roughness (Ra) of the surface layer including particles having a bimodal particle size distribution formed on one side of the release film may be 0.010 to 0.030 μm, and in order to make the surface roughness (Ra) of the surface layer including particles having a unimodal particle size distribution have a surface roughness of 0.001 to 0.015 μm, the particles having the unimodal particle size distribution may have an average particle size of 0.03 to 1 μm, specifically 0.05 to 0.8 μm, and may be added to the surface layer at a content of 300 to 5,000 ppm, and the particles having a bimodal particle size distribution may have an average particle size of 0.05 to 2 μm, specifically 0.1 to 1 μm, and may be added to the surface layer at a content of 300 to 5,000 ppm, but is not limited thereto as long as the object of the present invention is achieved. Furthermore, when the surface layer having the bimodal particle size distribution is a mixture of two different particles, the ratio of the larger particles to the smaller particles within the range of the average particle size and content may be 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or 10 or more, for example, in the range of 3 to 30. The content ratio is not limited as long as the object of the present invention is achieved, and the weight ratio of the larger particles to the smaller particles may be 0.1 to 10, but is not limited thereto.
[0043] In addition, the release film according to one embodiment having both surface layers with the above characteristics does not generate scratches when wound up, and even though it is a thin film, it has excellent windability and slippage around a roll, and has excellent smoothness, so that it is possible to provide a polyester-based release film that generates few pinholes when a thin ceramic sheet is produced by applying a ceramic slurry.
[0044] Furthermore, the release film can provide a film that can reduce the occurrence of pinholes due to transfer of surface roughness and the short defect rate of MLCCs (multilayer ceramic capacitors).
[0045] Furthermore, a polyester-based release film can be provided which generates little cutting powder even when the film is transported at high speed during production, and which generates little dust when the film is cut.
[0046] In one embodiment, the particles of the surface layer may be a mixture of one or more particles selected from inorganic particles and organic particles.
[0047] In one embodiment, the inorganic particles may be any one or more selected from metal oxides, metal carbides, metal sulfides, metal carbonitrides, etc. Examples include, but are not limited to, calcium carbonate, titanium oxide, aluminum oxide, silica, kaolin, and barium sulfate, but are not limited to inorganic particles used in this field. Examples of the organic particles may be any one or more mixtures selected from, but are not limited to, silicone resins, crosslinked acrylic particles, crosslinked polystyrene particles, benzoguanamine-formaldehyde resin particles, benzoguanamine-melamine-formaldehyde resin particles, and melamine-formaldehyde resin particles.
[0048] In one embodiment, the particles are effectively added in the form of a particle slurry dispersed in a glycol component during the synthesis of the polyester resin, since it has excellent dispersibility and can prevent re-agglomeration between particles, but is not limited thereto. That is, the particles may be added during the ester exchange reaction, or after the ester exchange reaction is completed and before the polycondensation reaction is started, but is not limited thereto.
[0049] In one embodiment, the release film can be produced by preparing particles during polymerization to obtain pellets, co-extruding the pellets, laminating them on both sides of a base film, and stretching them as necessary.
[0050] In addition, a separate master batch may be prepared using a polyester base resin and the particles, which may then be mixed with a polyester resin, melt-kneaded, co-extruded, and laminated on both sides of a base film. If necessary, a stretching process may be further performed after lamination.
[0051] The release film according to one embodiment of the present invention may be a biaxially oriented polyester film, but is not necessarily limited thereto.
[0052] In one embodiment, the biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching, and in the case of sequential biaxial stretching, it can be achieved by performing a process of stretching in the longitudinal direction (machine direction) and then stretching in the width direction (transverse direction). By performing such biaxial stretching, the strength and crystallization state in the longitudinal direction and the width direction can be made uniform, and cutting in each direction can be efficiently performed.
[0053] In one embodiment, the release film may be biaxially stretched 3 to 5 times in the machine direction and 4 to 6 times in the width direction, which is preferable because the thermal dimensional stability of the polymer structure is further increased at this stretch ratio, thereby reducing thermal shrinkage, but is not limited thereto.
[0054] In one embodiment of the present invention, the release film may be biaxially stretched, followed by heat treatment at 200 to 250° C. and relaxation by 1 to 10%. Specifically, relaxation may be imparted simultaneously with heat treatment, and more specifically, relaxation by 1 to 10%, more specifically, relaxation by 2 to 4% in the width direction may be performed. Within the above range, the film is maintained in a tensed state in the width direction, the density of the polymer structure is increased, and deformation due to heat can be reduced, which is preferable, but is not limited thereto.
[0055] According to one embodiment of the present invention, the release film has a giant protrusion count of 2.0 / mm2 measured using a three-dimensional surface roughness measuring device (Tokyo Seimitsu, Surfcom 590A-3DF-12) based on JIS B-0601. 2In the following cases, more specifically, 0.1 to 2 pieces / mm 2 The following cases are preferable because they satisfy the winding properties and running properties and therefore can provide a film that improves productivity, but are not limited thereto.
[0056] In one embodiment, the total thickness of the release film may be 10 to 50 μm, more specifically, 20 to 40 μm. The polyester film used as the base film of the release film for MLCC has a continuous tendency to be thinner in thickness, and is therefore suitable for application in the above range.
[0057] In one embodiment, the thickness ratio of the base film to the surface layers on both sides of the release film may be 50%:50%-90%:10%, more preferably 60%:40%-80%:20%. This range is preferable because it provides a film with excellent running properties, excellent slip properties, improved winding properties around a roll, and little cutting powder.
[0058] Furthermore, in the present invention, the thickness of the surface layers on both sides is not particularly limited, but it is more preferable that the thickness ratio is 1:0.8 to 1.2, since this can better achieve the effects of the present invention, but it is not limited thereto.
[0059] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the following examples and comparative examples are merely examples for explaining the present invention in more detail, and the present invention is not limited by the following examples and comparative examples.
[0060] The physical properties were evaluated as follows.
[0061] [Average particle size] The measurement was carried out using a particle size distribution analyzer (Beckman LS13 320).
[0062] Surface roughness (Ra) Based on JIS B-0601, the polyester film was cut into three sections, left, center, and right, and then a three-dimensional surface roughness measuring device (Tokyoseimitsu, Surfcom 590A-3DF-12) was used to measure the surface roughness at a measurement speed of 0.03 mm / sec, a stylus radius of 2 μm, a load of 0.7 mm / N, and a measurement area of 1.0 mm. 2 The measurements were performed under the condition of a cutoff value of 0.08 mm.
[0063] When the roughness curve is expressed as y = f(x) with the center line as the x-axis and the vertical direction as the y-axis, the calculation was made using the following formula.
[0064] JPEG2024546354000001.jpg1357
[0065] (L: Standard length (Cut-Off))
[0066] [Winding yield] The polyester films produced in the Examples and Comparative Examples were evaluated as follows by calculating the product yield relative to the input amount during production.
[0067] Winding yield (%) = product production volume / input volume x 100
[0068] ◎: Yield is 65% or more ○: When the yield is 55% or more but less than 65% △: When the yield is less than 55%
[0069] [Level of cutting dust generation] The produced film was slit into a width of 500 mm at a speed of 300 m / min. After slitting, the presence or absence of particles due to PET cutting powder in the 500 mm film roll was confirmed from the surface of the film roll. 2 If the number of hits was 0, it was rated as grade 1; if it was 1 to 3, it was rated as grade 2; if it was 4 to 6, it was rated as grade 3; if it was 7 to 9, it was rated as grade 4; if it was 10 to 12, it was rated as grade 5; and if it was 13 or more, it was rated as grade 6.
[0070] [Example 1] 1) Manufacture of polyester resin chips (1) 100 parts by weight of dimethyl terephthalate, 50 parts by weight of ethylene glycol, 400 ppm of magnesium acetate as electrostatic pinning agents, 200 ppm of calcium acetate, and 150 ppm of antimony trioxide as a polymerization catalyst were added to an esterification reactor, and an ester exchange reaction was carried out for 4 hours from room temperature to 230°C to produce a prepolymer BHET (bis-βterephthalate). Methanol, a by-product generated during the reaction, was discharged out of the reactor and separated through a distillation column, and ethylene glycol additionally generated after the esterification reaction was completed was also separated through a distillation column. At this time, 200 ppm of trimethyl phosphate was added as a thermal stabilizer, and the temperature was gradually raised to 285°C, and the pressure was reduced to 0.3 torr. Polycondensation reaction was carried out for 4 hours under high vacuum to produce polyethylene terephthalate (PET) resin chips with an intrinsic viscosity of 0.630 dl / g.
[0071] 2) Manufacturing of unimodal surface layer (release surface) polyester chip (2) 0.3% by weight of silica (particles A) having an average particle size of 0.3 μm was added to the polyester chips (1), and the mixture was melt-extruded using a twin-screw kneader to produce polyester chips (2).
[0072] 3) Manufacture of bimodal surface layer (back) polyester chip (3) 0.1% by weight of calcium carbonate (particles B) having an average particle size of 0.8 μm and 0.4% by weight of calcium carbonate particles having a particle size of 200 nm and 0.2 μm were added to the polyester chips (1), and the mixture was melt-extruded using a twin-screw kneader to produce polyester chips (3).
[0073] 4) Film manufacturing The core layer was made of polyester chips (1), the surface layer corresponding to the release surface was made of the chips (2), and the surface layer corresponding to the back surface was made of the chips (3), which were co-extruded into a three-layer film laminated with the release surface / core layer / back surface, and cast on a cooling roll to produce an unstretched sheet. At this time, the core layer was 80% by weight of the total film weight, and the surface layer was 20% by weight of the total film weight, and each surface layer was co-extruded with the same weight.
[0074] The mixture was melt-extruded through an extruder, and then rapidly cooled and solidified on a casting drum with a surface temperature of 20° C. to produce a sheet. The produced sheet was stretched 3.5 times in the machine direction and 4.0 times in the transverse direction at 95° C., and then heat-treated at 230° C. to produce a biaxially stretched film with a thickness of 30 μm. The physical properties of the produced film were measured and are shown in Table 2 below.
[0075] [Example 2] The same procedure was followed as in Example 1, except that the weight ratio of chip (2) to chip (3) was 1:2, and the weight ratio of the core layer to the surface layer was 70:30. The physical properties of the produced film were measured and are shown in Table 2 below.
[0076] [Example 3] The same procedure was carried out as in Example 1, except that the particle size of the chip (2) was 0.6 μm. As a result, the physical properties of the composite film were measured and are shown in Table 2 below.
[0077] [Example 4] The same procedure was carried out as in Example 1, except that the size of the large particles in the chip (3) was changed to 1.4 μm. As a result, the physical properties of the composite film were measured and are shown in Table 2 below.
[0078] [Comparative Example 1] The same procedure was carried out as in Example 1, except that the particles in chip (3) were single particles of 0.7 μm. As a result, the physical properties of the composite film were measured and are shown in Table 2 below.
[0079] [Table 1]
[0080] As shown in Table 1, even when two types of particles are used, when the particle size ratio between the particles and the bimodal particle size distribution are outside the range of the present invention, the production yield is poor. It was also confirmed that the generation of cutting powder increases, the winding yield decreases, and the surface roughness increases.
[0081] As described above, the present invention has been described using specific details and limited examples, but this is merely provided for a more general understanding of the present invention, and the present invention is not limited to the above examples. A person having ordinary knowledge in the field to which the present invention belongs can make various modifications and variations from such descriptions.
[0082] Therefore, the spirit of the present invention should not be limited to the described embodiments, and all things that are equivalent or have equivalent variations to the scope of the claims, as well as the scope of the claims described below, fall within the scope of the spirit of the present invention.
Claims
1. A polyester-based release film comprising a polyester base film, a polyester surface layer containing particles having a bimodal particle size distribution on one side thereof, and a polyester surface layer containing particles having a unimodal particle size distribution on the other side thereof laminated thereto.
2. 2. The polyester-based release film according to claim 1, wherein the surface layer containing the particles having a bimodal particle size distribution has a surface roughness (Ra) of 0.010 to 0.030 μm.
3. 2. The polyester-based release film according to claim 1, wherein the surface layer containing particles having a unimodal particle size distribution has a surface roughness (Ra) of 0.001 to 0.015 μm.
4. The polyester-based release film according to claim 2, wherein the average particle size of the particles in the surface layer containing the bimodal particles is 0.05 to 2 μm.
5. 4. The polyester-based release film according to claim 3, wherein the average particle size of the particles in the surface layer containing the particles having a unimodal particle size distribution is 0.03 to 1 μm.
6. 2. The polyester-based release film according to claim 1, wherein the content of the particles in the surface layer is 300 to 5,000 ppm.
7. 2. The polyester-based release film according to claim 1, wherein the particles are one or a mixture of two or more particles selected from inorganic particles and organic particles.
8. The polyester-based release film according to claim 7 , wherein the inorganic particles are one or more selected from the group consisting of metal oxides, metal carbides, metal sulfides, and metal carbonitrides.
9. The polyester-based release film according to claim 7, wherein the organic particles are any one or a mixture of two or more selected from silicone resins, crosslinked acrylic particles, crosslinked polystyrene particles, benzoguanamine-formaldehyde resins, benzoguanamine-melamine-formaldehyde resins, and melamine-formaldehyde resins.
10. The polyester-based release film according to claim 1 , wherein the polyester is a polyethylene terephthalate resin.
11. A method for producing a polyester-based release film, wherein the release film according to any one of claims 1 to 10 is produced by coextrusion.
12. The method for producing a polyester-based release film according to claim 11, wherein the polyester-based release film is produced by stretching after the co-extrusion.
Citation Information
Patent Citations
Support film for manufacturing plastic film by cast method
JP2006069119A
Biaxially oriented polyester film for mold release
WO2014061410A1
Polyester film
WO2018062397A1
Alignment film for transferring liquid crystal compound alignment layer
WO2020085308A1
